Antibacterial polymethylmethacrylate (PMMA)/ beta tri calsium phosphate/ zinc oxide composites for craniofacial reconstruction - Hamad, Wan Nur Fadilla Wan (2022)
Polymethylmethacrylate (PMMA) is commonly used in dental and bone reconstruction applications due to the excellent properties such as biocompatible, biologically inert and rigid. In craniofacial, traumatic injuries will result to the defect of underlying brain. Somehow, after reconstruction of scull using PMMA, the infection may occur. Thus, incorporation of antibacterial agent such as beta tricalcium phosphate (β-TCP) to the PMMA is desirable to eliminate infection. Also, the presence of β-TCP to the composites is one of the alternatives to promote cell growth to the surrounding bone tissue. Hence, in this study, PMMA composites fabricated with specified percentages of filler content of β-TCP and Zinc Oxide. The composites divided into three groups of different percentages of 5, 10, 15% β-TCP without ZnO, and another two groups, 2.5% and 5% ZnO were added 15% β-TCP. The size of β- TCP was approximately 1-5μm and ZnO was in nano size (256nm). The mechanical characteristics, chemical bonding, and physical properties of the specimen were next assessed. The characterization of specimen was then evaluated for mechanical properties, chemical bonding, physical properties. Observations of the microstructure of the fracture surface were performed by Field Emission scanning electron microscopy (FESEM). Chemical groups existed were confirmed with analysis of Fourier Transmission InfraRed (FTIR). The mechanical properties showed the improvement for PMMA composites. There is significant difference detected between PMMA pure and PMMA composites in physical properties. The cytotoxicity effect was investigated through 3-(4, 5-dimethylthiazoyl)-2-5 diphenyl-tetrazolium bromide (MTT assay), using human fetal osteoblast cell (hFOB). The hFOB cultured with 25 mg/ml PMMA filled 15% βTCP and 5% ZnO demonstrated the highest cell viability (132.73%). The percentages of cell viability of samples with 50 mg/ml and below showed no cytotoxicity effect due to their value of cell viability were more than 70%. The antibacterial properties of the PMMA composite were evaluated using agar diffusion and growth curve methods against Gram positive (Staphylococcus aureus) and gram negative (Pseudomonas aeruginosa). A significant difference was observed with the incorporation of ZnO filler in the agar diffusion test. The antibacterial property of PMMA composites were further evaluated with a growth curve and significant antibacterial activity was found on PMMA composites with 2.5% and 5% of ZnO filled. In conclusion, PMMA composites at 2.5% and 5% ZnO, are promising biomaterials that suit to be applied as implants in craniofacial reconstruction.